2004
DOI: 10.1159/000079415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Interleukin-2 Infusion and Stressors on Sickness Behaviors and Neurochemical Change in Mice

Abstract: Objectives: Major depression is associated with increased circulating interleukin-2 (IL-2) levels, and IL-2 immunotherapy may provoke depressive symptoms, leading to the suggestion that this cytokine may contribute to the evolution of affective disorders. Although depression is a relatively chronic condition, and immunotherapy involves repeated cytokine administration, animal studies have typically assessed the consequences of acute cytokine treatment. The present investigation assessed several behavioral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
(55 reference statements)
1
9
0
1
Order By: Relevance
“…In contrast, one study reported an elevation in whole hypothalamic levels of NE (Prieto et al, 2003) and two others have reported elevations in NE utilization within the PVN (Patterson et al, 2010; Sudom et al, 2004). The primary differences among these studies is that for the whole hypothalamic assay, the analysis was performed 24 h following the final stressor, whereas in the study by Haidkind et al (2003), analysis was done 7 days following the final stressor, suggesting that a recovery of function may have occurred during this period.…”
Section: Neurochemical Systemsmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, one study reported an elevation in whole hypothalamic levels of NE (Prieto et al, 2003) and two others have reported elevations in NE utilization within the PVN (Patterson et al, 2010; Sudom et al, 2004). The primary differences among these studies is that for the whole hypothalamic assay, the analysis was performed 24 h following the final stressor, whereas in the study by Haidkind et al (2003), analysis was done 7 days following the final stressor, suggesting that a recovery of function may have occurred during this period.…”
Section: Neurochemical Systemsmentioning
confidence: 91%
“…When specific subregions of the hypothalamus are examined, there appears to be great consistency of results. In general, data suggest that there is no effect of CMS on serotonergic transmission in the paraventricular nucleus of the hypothalamus (Tannenbaum and Anisman, 2003; Sudom et al, 2004; Tannenbaum et al, 2002; Patterson et al, 2010), while in the median eminence, CMS has been reported to increase 5-HT utilization (Tannenbaum and Anisman, 2003). The only published study to date that has examined 5-HT receptor binding in the hypothalamus following CMS reported reduced 5-HT 1A receptor binding following CMS (Jang et al, 2004).…”
Section: Neurochemical Systemsmentioning
confidence: 99%
“…These include two series of studies reporting a decreased intake of palatable food intake in brief (3 or 5 min) sessions in rats [89,95,96,98] , and a similar effect in mice [82,97] , and one study that actually reported an increase in total intake of palatable food, but in the context of a very slow rate of eating in a much longer (30 min) session [98] . In the studies by Di Chiara and colleagues [100,101] , the dependent measure was dopamine release in nucleus accumbens shell and prefrontal cortex in response to the taste of a palatable food: these measures were both decreased by CMS.…”
Section: Effects Of Cms On Other Measures Of Hedonic Reactivitymentioning
confidence: 99%
“…The anorexigenic outcomes of the APR can be mimicked by externally administering inflammatory cytokines to the periphery or CNS, with synergistic effects occurring between cytokines in some cases [78,79,80,81,82,83,84,85,86]. The resultant alterations in feeding behaviours are typically observed as reductions in meal size, duration, and frequency, and longer inter-meal intervals [80,85,87].…”
Section: The Role Of Cytokines In Weight Regulationmentioning
confidence: 99%